1996
DOI: 10.1093/jac/37.5.911
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activities in vitro and in vivo of transition element complexes containing gold(I) and osmium(VI)

Abstract: Metal compounds have been used as antibacterial agents for centuries. The in-vitro activity of two metal containing complexes, one gold, the other osmium, was investigated using a panel of clinically isolated bacteria and Candida albicans. Twenty strains of each organism were used and MIC and MBC values determined using the agar plate dilution method. Protein binding effects on the activity of the compounds were also investigated using media supplemented with 5% human blood. In-vivo activity of the two compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 16 publications
0
44
0
1
Order By: Relevance
“…In this last field, the compounds under investigation include a major collection of the type R 3 PAuL, in which the gold atom is coordinated to a phosphine ligand and L is an O- [26,27], N- [28,29], Cl- [30] or S- [29,[31][32][33][34][35] 2 ], Na 3 [Au(mna) 2 ] (H 2 mna 02-mercaptonicotinic acid) [13] and the cationic complexes [Au(L) 2 ](NO 3 ) 3 (L01-[2-(acridin-9-ylamino)ethyl]-1,3-dimethylthiourea) [34]. For the latter ligand, compounds of the type [Au(L)]Br, [Au(L)] SCN and [Au(L)]Cl were also prepared [34] and the coexistence of an S-donor ligand and a Cl ligand was also described for [LAuCl] (where L 02,3-diphenyl-1,3,4-thiadiazolium-5-thiolato-S exo ) [36].…”
Section: (L)] [Hq][ag(l)] (Hq0diisopropylammonium)mentioning
confidence: 99%
“…In this last field, the compounds under investigation include a major collection of the type R 3 PAuL, in which the gold atom is coordinated to a phosphine ligand and L is an O- [26,27], N- [28,29], Cl- [30] or S- [29,[31][32][33][34][35] 2 ], Na 3 [Au(mna) 2 ] (H 2 mna 02-mercaptonicotinic acid) [13] and the cationic complexes [Au(L) 2 ](NO 3 ) 3 (L01-[2-(acridin-9-ylamino)ethyl]-1,3-dimethylthiourea) [34]. For the latter ligand, compounds of the type [Au(L)]Br, [Au(L)] SCN and [Au(L)]Cl were also prepared [34] and the coexistence of an S-donor ligand and a Cl ligand was also described for [LAuCl] (where L 02,3-diphenyl-1,3,4-thiadiazolium-5-thiolato-S exo ) [36].…”
Section: (L)] [Hq][ag(l)] (Hq0diisopropylammonium)mentioning
confidence: 99%
“…The antimicrobial activity of metal (II) complexes such as copper (II), zinc (II) and iron (II) (Osowole et al, 2012;Sharma et al, 2011;Chohan et al, 2006) against the vast range of pathogens such as bacteria and fungi has been recognized for a long time (Elsome et al, 1996;Osowole et al, 2012;Sharma et al, 2011). It was demonstrated that conidial germination and development of Helminthosporium solani could completely be inhibited by Iron salts (Mimee et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…As therapeutic agents, usage of metal ions increases the drug action as well as coordination of metal ions to drug molecules also raise the drug efficacy [11,12]. The role of metal complexes has been recognized from centuries in antimicrobial activities and most fundamental breakthroughs are also known by them in medical history [13].…”
Section: Introductionmentioning
confidence: 99%